2018
DOI: 10.1097/tp.0000000000002372
|View full text |Cite
|
Sign up to set email alerts
|

The Selective RNA Polymerase I Inhibitor CX-5461 Mitigates Neointimal Remodeling in a Modified Model of Rat Aortic Transplantation

Abstract: Background Transplant vasculopathy is a major cause of chronic rejection of transplanted organs. In the present study, we examined the effects of CX-5461, a novel selective inhibitor of RNA polymerase I, on development of transplant vasculopathy using a modified model of rat aortic transplantation. Methods The thoracic aortas from Fischer rats were transplanted into the abdominal cavity of Lewis rats. CX-5461 was mixed in pluronic gel and administered v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
7
22
0
Order By: Relevance
“…Potent inhibitory effects of CX-5461 against pathological arterial remodelling have been observed in our previous studies in rat carotid arteries and aortae with angioplasty-or transplantation-induced injuries (Dai et al, 2018;Ye et al, 2017). Based on these data and those from the present study, we suggest that the beneficial effects of CX- although G1/S blockade predominates in the latter comparing with G2/M blockade in the former (Ye et al, 2017).…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lsupporting
confidence: 86%
See 4 more Smart Citations
“…Potent inhibitory effects of CX-5461 against pathological arterial remodelling have been observed in our previous studies in rat carotid arteries and aortae with angioplasty-or transplantation-induced injuries (Dai et al, 2018;Ye et al, 2017). Based on these data and those from the present study, we suggest that the beneficial effects of CX- although G1/S blockade predominates in the latter comparing with G2/M blockade in the former (Ye et al, 2017).…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lsupporting
confidence: 86%
“…It is clear that disruption of rDNA transcription triggers a distinct cellular stress response known as nucleolar stress, resulting in activation of the p53 pathway (Boulon et al, 2010;Yang et al, 2018). In contrast to the current paradigm which emphasizes stabilization and accumulation of p53 protein, following induction of nucleolar stress, we have repeatedly observed that CX-5461 had no major effects on total p53, but induced a robust response of p53 phosphorylation in a variety of cells (Dai et al, 2018;Ye et al, 2017), including human PASMCs, as used in the present study. Moreover, in the present study, we have confirmed that the cell cycle blockade in response to CX-5461 in human PASMCs is at least partly dependent on p53 as observed previously (Ye et al, 2017).…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lungsmentioning
confidence: 66%
See 3 more Smart Citations